Meaning Of Youth In The 2019 Presidential Election Campaign News On Social Media - Sri Budi Lestari; Hedi Pudjo Santosa; Primada Qurota Ayun (Jurnal Ilmu Komunikasi, 2019)
The development of technology makes the lives of adolescents integratedwith social media and digital. The ease of accessing information through digitalmedia, makes teens fall into the trap of being over-communicated, and even tendsto only share information without being filtered first. How teenagers interpret thenews about the 2019 Presidential Election campaign that they received is importantto be observed so that youth do not get lost in the information rush. This qualitativestudy uses a reception analysis approach through depth interviews with 14 seniorhigh school student informants in Semarang, aimed at knowing how teenagersinterpret the 2019 Presidential Election campaign news information on socialmedia. The results inform that the informants are media literate and are able tointerpret political information according to their understanding. Even though someof them stated that they did not like political news, during the presidential andpresidential elections in April 2019, all took part in making their choices.